2023
DOI: 10.1038/s41588-023-01504-w
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC3B regulates R-loops and promotes transcription-associated mutagenesis in cancer

Jennifer L. McCann,
Agnese Cristini,
Emily K. Law
et al.

Abstract: The single-stranded DNA cytosine-to-uracil deaminase APOBEC3B is an antiviral protein implicated in cancer. However, its substrates in cells are not fully delineated. Here APOBEC3B proteomics reveal interactions with a surprising number of R-loop factors. Biochemical experiments show APOBEC3B binding to R-loops in cells and in vitro. Genetic experiments demonstrate R-loop increases in cells lacking APOBEC3B and decreases in cells overexpressing APOBEC3B. Genome-wide analyses show major changes in the overall l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 91 publications
1
6
0
Order By: Relevance
“…According to the hypothesis that unresolved TRCs give rise to DSBs and ultimately to genome instability, we found that R-loops-dependent TRC formed consequently to ANP32E overexpression were significantly enriched in proximity of known CFSs. The biological relevance of this finding is further supported by recent results obtained from patients of breast adenocarcinoma relating APOBEC3-dependent kataegis in R-loop regions with similar proximity from structural variants breakpoints 67 .…”
Section: Discussionsupporting
confidence: 76%
“…According to the hypothesis that unresolved TRCs give rise to DSBs and ultimately to genome instability, we found that R-loops-dependent TRC formed consequently to ANP32E overexpression were significantly enriched in proximity of known CFSs. The biological relevance of this finding is further supported by recent results obtained from patients of breast adenocarcinoma relating APOBEC3-dependent kataegis in R-loop regions with similar proximity from structural variants breakpoints 67 .…”
Section: Discussionsupporting
confidence: 76%
“…We show that the loss of the central E3 ligases, UBR4, UBR5, and HUWE1 stabilizes A3B and A3H-I proteins, resulting in their accumulation and eventually increased APOBEC-related mutational burden. Our findings reveal a previously unconsidered layer of regulation of cellular A3 protein levels, which may broaden the mutational landscape in late-stage cancer, and affect development of therapy resistance 32,[61][62][63][64] .…”
Section: Discussionmentioning
confidence: 83%
“…Although the importance of transcription bubbles as APOBEC3 targets in human cells remains unresolved (Nordentoft et al 2014;Kazanov et al 2015;Chervova et al 2021;McCann et al 2023), it is clear that in the humanized yeast models for APOBEC3A, APOBEC3B, and APOBEC3C there are different biases to the 5' regions of tRNA and pol II genes. APOBEC3A and 3C show similar biases to tRNA and pol II genes, whereas APOBEC3B lacks a bias to pol II genes and causes a much smaller proportion of deaminations at tRNA genes (Figure 5c and f).…”
Section: Discussionmentioning
confidence: 99%
“…2015; Chervova et al . 2021; McCann et al . 2023), it is clear that in the humanized yeast models for APOBEC3A, APOBEC3B, and APOBEC3C there are different biases to the 5’ regions of tRNA and pol II genes.…”
Section: Discussionmentioning
confidence: 99%